VERTEBRAL PLATEAU DEGENERATION AFTER LUMBAR MICRODISCECTOMY: PROSPECTIVE COHORT - MATHEUS NEVES CASTANHEIRA; GUILHERME PIANOWSKI PAJANOTI; MICHEL KANAS; FELIPE NEVES MONTEIRO; DELIO EÜLALIO MARTINS; MARCELO WAJCHENBERG; NELSON ASTUR (Coluna/Columna)
ABSTRACT Objective: To examine the evolution of degenerative changes in the vertebral plateau of patients with lumbar disc herniation undergoing microdiscectomy, emphasizing the progression of Modic type 1 and 2 changes. Methods: A Prospective cohort study was conducted at a single center, including patients who underwent microdiscectomy between 2017 and 2019. Magnetic resonance imaging (MRI) was acquired preoperatively and 12 months after the intervention. Modic changes were classified by two independent radiologists following the criteria established by Wang et al. Statistical analysis included chi-square tests, Fisher’s exact test, and Wilcoxon tests, with a significance level of p<0.05. Results: A total of 112 patients were analyzed, of which 70 completed one-year follow-up. Preoperatively, 14 patients had no Modic changes, while 45 had Modic type 1 and 18 had Modic type 2. After one year, 5 patients without initial changes developed Modic type 1 or 2. In patients with Modic type 1, a statistically significant reduction in the affected area was observed (mean 211.6 mm2 to 159.1 mm2; p=0.001). In cases of Modic type 2, no significant change in the extent of the lesion was identified. Conclusion: Microdiscectomy impacts the progression of Modic changes, particularly by reducing the lesion area in Modic type 1, suggesting a possible effect on modulating the inflammatory response and the course of vertebral endplate degeneration. Further studies are needed to elucidate this association’s underlying mechanisms and clinical relevance. Level of Evidence III; Prospective Cohort Study.